Evaluation of prednisolone treatment in the acute phase of neuralgic amyotrophy: an observational study. Issue 10 (24th March 2009) - van Eijk, J J J; van Alfen, N; Berrevoets, M; van der Wilt, G J; Pillen, S; van Engelen, B G M
Abstract : Background: Effective treatment for neuralgic amyotrophy (NA), a disabling brachial plexus syndrome of supposed immunomediated origin, is currently lacking. Given the circumstantial evidence of a beneficial effect of prednisolone on pain and paresis, this report evaluates the effects of prednisolone treatment administered in the acute phase in a retrospective case series of 50 NA patients. Methods: Baseline variables (eg, age, sex, type of NA and number of attacks), treatment variables (eg, time until treatment, regimen and use of analgesics) and outcome measures (eg, duration and severity of pain, time course and severity of paresis and functional outcome) were statistically analysed and compared with a historical control group of 203 untreated NA patients. Results: The baseline characteristics of the two patient groups were comparable. The median time until initial pain relief was lower in the study group (12.5 days vs 20.5 days), and a significantly higher percentage already recovered strength in the first month of treatment (18% vs 6.3%; p = 0.011). Twelve per cent had fully recovered within 1 year, while this was 1% for the controls (p<0.001), with the proportion reporting a "good" 12-month outcome also being higher (44% vs 10.7%; p<0.001). Side effects were reported by 20%, but none led to a discontinuation of treatment. Conclusion: Oral prednisolone seems effective in the acute phase of neuralgic amyotrophy with the current results supporting previous case reports. A regimen of oral prednisolone is therefore recommended in the acute phase of the syndrome pending a prospective, randomised trial verifying the results obtained.